2020
DOI: 10.3389/fphar.2020.00435
|View full text |Cite
|
Sign up to set email alerts
|

The Noradrenergic System in Parkinson’s Disease

Abstract: Nowadays it is well accepted that in Parkinson's disease (PD), the neurodegenerative process occurs in stages and that damage to other areas precedes the neuronal loss in the substantia nigra pars compacta, which is considered a pathophysiological hallmark of PD. This heterogeneous and progressive neurodegeneration may explain the diverse symptomatology of the disease, including motor and non-motor alterations. In PD, one of the first areas undergoing degeneration is the locus coeruleus (LC). This noradrenergi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
67
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(69 citation statements)
references
References 207 publications
0
67
1
1
Order By: Relevance
“…As mentioned previously, noradrenergic mechanisms are involved in the non-motor symptoms observed in PD patients. Idazoxan, a presynaptic alpha2-adrenergic antagonist, enhances NA release, increasing the noradrenergic activity that modulates L-DOPA effects (for a review, see [ 93 ]). Recently, atomoxetine, a NA transporter blocker, has been shown to increase the standing blood pressure and to reduce OH symptoms when compared with placebo in patients with neurogenic OH [ 94 ].…”
Section: Interaction Between Small Heat Shock Protein 27 and α-Synmentioning
confidence: 99%
“…As mentioned previously, noradrenergic mechanisms are involved in the non-motor symptoms observed in PD patients. Idazoxan, a presynaptic alpha2-adrenergic antagonist, enhances NA release, increasing the noradrenergic activity that modulates L-DOPA effects (for a review, see [ 93 ]). Recently, atomoxetine, a NA transporter blocker, has been shown to increase the standing blood pressure and to reduce OH symptoms when compared with placebo in patients with neurogenic OH [ 94 ].…”
Section: Interaction Between Small Heat Shock Protein 27 and α-Synmentioning
confidence: 99%
“…Lack of DA causes movement control alteration, leading to typical motor symptoms, such as resting tremor or stiffness. Beside for the SNc and the dopaminergic system, other neurotransmission systems can be affected by α-synuclein (α-syn) deposition, including glutamatergic, noradrenergic, serotoninergic, cholinergic, and histaminergic neurons [4]. In fact, the first brain area affected by α-syn deposition appears in the anterior olfactory structures and the dorsal motor nucleus of the vagus nerve, which comprises stage 1 according to Braak theory; afterwards the raphe system and the locus coeruleus can suffer of α-syn deposition (stage 2) [5].…”
Section: Parkinson's Disease Outlinementioning
confidence: 99%
“…The progression described by Braak shows that noradrenergic and serotoninergic systems are also disturbed in PD. Additionally, specific clinical signs can be explained by noradrenergic dysfunction, which can be significant and anticipate onset of motor symptoms [4]. It is mandatory to keep in mind that the loss of DA in the nigrostriatal pathway is secondary to the axonal degeneration caused by homeostatic disturbances in the SNc [6].…”
Section: Parkinson's Disease Outlinementioning
confidence: 99%
“…Both pupillary response and activation of noradrenergic neurons in the locus coeruleus have been shown to increase in a correlated manner with increased cognitive workload ( Varazzani et al, 2015 ). Although locus coeruleus is one of the first areas undergoing degeneration due to the PD pathophysiology ( Micieli et al, 1991 ; Paredes-Rodriguez et al, 2020 ), dopamine replacement therapy has been shown to restore pupillary response in individuals with PD ( Manohar and Husain, 2015 ). Also, a previous study showed that pupillary response during “ON” medication reflects cognitive workload in individuals with PD ( Kahya et al, 2018a ).…”
Section: Introductionmentioning
confidence: 99%